2020
DOI: 10.1186/s12885-020-07452-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk of HPV-related extra-cervical cancers in women treated for cervical intraepithelial neoplasia

Abstract: Background The aim was to estimate the risk of subsequent extra-cervical Human Papillomavirus (HPV) related cancer in patients surgically treated for high grade cervical intraepithelial neoplasia (CIN 2–3). This is the first study in Italy investigating the occurrence of extra-cervical tumors in this cohort of patients. Methods 3184 patients surgically treated for CIN2–3 since 1992 at the Department of Surgical Sciences of University of Torino were considered. The risk of HPV-related cancer was calculated as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 50 publications
2
34
0
1
Order By: Relevance
“…Studies encompassing lower grades of CIN, that is, CIN1-3 [ 55 , 56 ] or CIN2-3 [ 40 , 71 ], confirmed the above observations with a single exception, an Italian hospital-based cohort study of patients with CIN2-3 [ 71 ] in which the incidence increase was moderate and not significant. A study reported from the British Columbia associated a diagnosis of CIN2-3 with a SIR for VC of 2.90 [ 47 ].…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…Studies encompassing lower grades of CIN, that is, CIN1-3 [ 55 , 56 ] or CIN2-3 [ 40 , 71 ], confirmed the above observations with a single exception, an Italian hospital-based cohort study of patients with CIN2-3 [ 71 ] in which the incidence increase was moderate and not significant. A study reported from the British Columbia associated a diagnosis of CIN2-3 with a SIR for VC of 2.90 [ 47 ].…”
Section: Resultsmentioning
confidence: 67%
“…The number of original articles selected was 63. Six more original articles were identified through snowballing for a total of 69 articles [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis further identi ed clinical presentation of chronic lower abdominal pain (speci cally in older women), indication of contraceptives, smoking and menopause. In fact, [15] describe smoking as the mutual risk factor and most plausible root of correlation between cervical and lung or bladder cancers as well as con rmed a formidable association between oral and cervical HPV related lesions in smoking patients than non-smokers. Data from a study by [16] showed the need to identify post-menopausal women at risk of developing CIN or cancer prior to completion of screening programme.…”
Section: Heterogeneity Between Screening Modalitiesmentioning
confidence: 91%
“…As per the global cancer statistics, cervical cancer is ranked as the fourth most common cancer in women ( https://www.who.int/health-topics/cervical-cancer#tab = tab_1 ) ( Das, 2021 ). Diagnosis and treatment of the preinvasive lesions at cervical intraepithelial neoplasia (CIN) stages would render the disease curable (Castle et al, 2017 ) and possess tremendous importance in the cervical cancer control agenda ( Preti et al, 2020 ). Although the cervical cancer screening and prophylactic vaccination against HPV have achieved some success in prevention and early treatment in the most affluent countries, cervical cancer remains the leading cause of mobility and mortality for women in countries with inadequate health services and vaccination coverage ( Bray et al, 2018 ; Beddoe, 2019 ; Canfell et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%